Role of Phytoplankton and Zooplankton Diversity as Bioindicators in Assessing Water Quality of Surface Water Bodies in Mahendergarh District, Haryana (International Journal of Environmental Sciences, 2025)
The current study will estimate biodiversity of phyto and zooplanktons based on the surveys of three surface water bodies (JLN Canal (Haryana state, Mahendergarh district), Chalak Nala (Haryana state, Mahendergarh district) and Khatoti Khurd Pond (Haryana state, Mahendergarh district)) to estimate biodiversity in each of the three water bodies and carry out the two-year difference (2022Rec2024Rec). The water samples were then collected seasonally (pre-monsoon, monsoon and post-monsoon season) to be able to understand the association pattern between water condition and the diversity of the planktons in such water bodies. A comprehensive analysis of the various shape of algae has been done on four larger groups which are Chlorophyceae (green algae), Cyanophyceae (blue-green algae), Bacillariophyceae (diatoms) and Euglenophyceae (euglenoids). At the same time, the diversity of the zooplankton was assessed based on such taxonomies as Rotifera, Cladocera, Protozoa as well as Copepoda. It has been ascertained in the research that, the most diverse and rich phytoplankton and zooplankton site is Chalak Nala (Site 2) and this is a sign that such site is nutrient rich and eutrophic. JLN Canal (Site 1) on the other hand presented the lowest amount of diversity, as well as the indication of a high water quality. It was made apparent that the variations of the seasons were present and higher quantities of plankton were observed during the pre-monsoon times when the quantity of heat and the increased access of nutrients prevailed. The results help establish why plankton community should be monitored as a pointer to the health condition of the aquatic ecosystems, or as a pointer to the water purity. The outcomes also highlight the importance of effective interventions on water quality management in an attempt to worsen such important water bodies further.